What is important for high quality rural health care? A qualitative study of rural community and provider views in Aotearoa New Zealand - Carol Atmore; Susan Dovey; Robin Gauld; Tim Stokes (James Cook University, 2023)
Introduction: While the general principles of healthcare quality are well articulated internationally, less has been written about applying these principles to rural contexts. Research exploring patient and provider views of healthcare quality in rural communities is limited. This study investigated what was important in healthcare quality particularly for hospital-level care for rural communities in Aotearoa New Zealand. Methods: A pragmatic qualitative study was undertaken in four diverse rural communities with access to rural hospitals. Data were gathered through eight community and indigenous (Māori) focus groups (75 participants) and 34 health provider interviews, and analysed thematically. Results: Two study sites had large Māori populations and high levels of socioeconomic deprivation, whereas the other two sites had much lower Māori populations and lower levels of socioeconomic deprivation, but further travel distances to urban facilities. Rural hospitals in the communities ranged from 12 to 80 beds and were both government and community trust owned. A theme of the principles of high quality rurally focused health services was developed. Nine principles were identified: (1) providing patient- and family-centred care that respected people's preferences for where treatment was provided; (2) providing services as close to home as could be done well; (3) quality was everybody's job; (4) consistent care across settings, with reduction on unwarranted variation; (5) team-based care across distance, with clear communication and processes between different facilities working together; (6) equitable health care particularly for Māori, and then for the whole rural community; (7) sustainable service models, particularly for workforce, as a counterbalance to 'closer to home'; (8) health networks to improve patient flow, and reduce waste; and (9) value was more than value for money, and including valuing respectful, timely care. Another theme around rural and urban healthcare quality was developed. While the nature of care was different in different settings, patient experience should be the underlying measure of quality, and quality measures needed to be interpreted in the context of local circumstances, with rural-specific quality measures where appropriate. Conclusion: The researchers developed principles of healthcare quality specific to rural communities regarding patient and family preferences for where care was received, a broader focus on value beyond value for money and a strong focus on equity for indigenous people. These principles add to the rural principles previously described. Patient experience should be the underlying focus of quality, while noting that the nature of health care provided in rural and urban settings is different. The present study's findings support the concept that quality measures should be interpreted in the context of local circumstances, with the development of rural-specific measures. The authors hope the findings, when locally contextualised, will assist health policy makers, planners, providers and community leaders as they strive to improve the quality of health services for their rural communities.